(untitled) (Bangladesh Journal of Zoology, 2015)
A comparative account of haemato-biochemical profiles of an indigenus (IND) and five chicken breeds: viz. Cobb 500 (COB), cockerel (COC), Fayoumi (FAY), Rhode Island Red (RIR), and Sonali (SON, derived from RIR cock × FAY hen), has been presented. The haematological profile included total counts (TC) of RBC, WBC, platelets, haemoglobin (Hb%) and ESR and differential counts (DC) of WBC included neutrophils, eosinophils, lymphocytes, monocytes and basophils. All the haematological parameters except WBC, ESR and basophils showed significant difference among the breeds (P < 0.01). Vital biochemical parameters from blood sera such as calcium, cholesterol, creatinine, glucose and urea also showed significant difference among the chicken breeds (P < 0.05). The haematobiochemical parameters, however, were not significantly correlated (P > 0.05) with each other among the chicken breeds. Except for cholesterol vs. urea in IND, none of the correlations tested for haemato-biochemical profiles of the experimental chickens was found significant. Relevance of this study in relation to health, clinico-pathology and improved breeding strategies of the poultry species in the country has been discussed. Bangladesh J. Zool. 41(2): 135-144, 2013